Health Education About the Dangers of Gadgets for the Psychosocial Development of Children - Dewi Eka Putri; Randy Refnandes; Yara Agustin (Warta Pengabdian Andalas, 2019)
As many as 33.3% of school-age children have deviant psychosocial developments such as withdrawing from other children, fear of self-performance, antisocial behavior accompanied by verbal and physical violence, including bullying. The use of unlimited gadgets is one of the factors causing this abnormal psychosocial development. Gadgets that are used among school-age children are generally for playing online games that are full of violent content, and often verbal abuse occurs when interacting with other users when playing. In the context of promotion and prevention efforts, this community service activity carried out in the form of providing health education about the dangers of gadgets for the psychosocial development of children using the Brain Storming method and group discussions with children and their parents through the Community Mental Health Nursing (CMHN) case management approach. In this activity, measurements carried out on the knowledge of parents and children before and after health education. There were 30 participants, 15 parents, and 15 children. The instrument used was a gadget danger knowledge questionnaire for the mental health of school-age children. The statistical test used was a paired t-test with the results of the influence of health education on the dangers of gadgets on parent and child knowledge (p <0.05) — increase knowledge scores on parents by 2.13 points with scores before 7.40 and after 9.53. In children, the increase in knowledge scores by 2.54 points with a score before 6.73 and after 9.27. It recommended that parents to further enhance the provision of stimulation in the psychosocial aspects of children by encouraging children to play with peers and limit children in using gadgets 2-3 hours a day. Keywords: Gadgets, Stimulation, School Age